Lexical reconstruction of Proto-Patani: the case of Narathiwat variants - Miss Deela Sinur,; Shahidi A. Hamid,; Rahim Aman, (Penerbit Universiti Kebangsaan Malaysia, 2025)
The Patani Malay is one of the dialects spoken in southern Thailand. Its distribution covers the region of Pattani, Yala, and Narathiwat, as well as parts of Songkhla, including the Sebayoi, Thepa, Nathawi, and Chana. Based on studies on the Patani Malay discussed earlier, it can be concluded that no studies have been conducted on the proto form of the Patani Malay, especially in the Narathiwat region. Therefore, this study aims to reconstruct the lexical form of the Patani Malay of Narathiwat (PMN) to obtain its proto form. The approach used in this study is a descriptive qualitative method based on a historical linguistic approach. This research applies two central studies to obtain linguistic information and data: library and field research. The study involved six villages as a study location, namely Kampung Kresor (KRS), Buketa (BKT), Puyok (PYK), Munok (MNK), Benae Luwas (BNL) and Aikubu (AKB). The PPMN lexical reconstruction shows that it sometimes has a similar form of the word with the Proto-Malayic (PM) and sometimes exists as a direct inheritance of PM. However, the similarity of the PPMN still exists as a proto dialect with its own lexical. Therefore, the findings of this study are beneficial as input for the subsequent research of classifying the PPMN to determine the distant-close relationships between the dialect variants.